IMPLEMENTASI MAHAR MENGGUNAKAN HAFALAN AL-QU’RAN DALAM PERSPEKTIF MAQASHID SYARIAH - Sholeh, Aziz; Zulbaidah, Zulbaidah; Faisal, Enceng Arif (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2023)
AbstractThis study discusses the concept of dowry using memorization of the Koran in Maqashid al-Syariah. The method used in this research is qualitative and the data collection technique uses a libraryresearch. Meanwhile, qualitative data analysis techniques use data reduction, data presentation, and drawing conclusions or verification. The results of the study show that in Islamic law, dowry refers to gifts given by the man to the woman as part of the marriage process, so that it is one of the important elements in marriage in Islam and has a deeper meaning than just material values. Mahar can have several types, depending on the form, value, or characteristics of the gift. As for memorizing verses of the Qur'an as a marriage dowry in the concept of Maqashid al-Syariah, it can be seen from its purpose, namely Hifz al-Din, Hifz al-Nafs, Hifz al-Aql, Hifz al-Nasl, and Hifz al-Mal. Meanwhile, the implications of using memorized verses of the Qur'an as a marriage dowry in society can have various impacts depending on the cultural context, religion, and social views of the community.